Muscle architectural and performance adaptations following an 8-week sprint-focused training intervention - Luke R. Stutter; Steven Duhig; David L. Carey; Matthew W. Driller; Charlie J. Davids; Lachlan P. James (European Journal of Applied Physiology, 2026)
Muscle fascicle length is a key determinant of sprint performance, with lengthening adaptations observed following eccentric strength training or combined sprint and resistance interventions. However, whether sprint-focused training can induce meaningful architectural adaptations, independent of concurrent sport-related training, remains unclear. Fourteen participants (10 female, 4 male; age 21.6 ± 3.3 years; body mass 68.0 ± 11.8 kg) completed an 8-week speed training intervention using a single-group design. Training sessions consisted of maximal velocity and resisted sprinting, technical acceleration drills, and a low volume of back squats to maintain baseline strength, with no additional lower-body training permitted. Vastus lateralis (VL) and biceps femoris long head (BFlh) fascicle length was estimated using 2-D ultrasound, alongside 40-metre sprint, jump and maximal strength tests. Significant increases in fascicle length were observed in the BFlh (left: 2.23 cm, 95%CI 1.75 to 2.70, p < 0.0001; right: 2.44 cm, 95%CI 1.99 to 2.90, p < 0.0001) and VL (left: 0.32 cm, 95%CI 0.83 to 1.81, p < 0.0001; right: 1.48 cm, 95%CI 0.95 to 2.01, p < 0.0001). Large effect sizes were evident across all muscles ( g = 1.40–2.03, 95% CI 0.86 to 2.46). No significant main effects for time were observed for sprint, jump or strength outcomes, however, small effect size improvements were evident for flying 10-m ( g = -0.27, 95% CI -0.46 to -0.09) performance. These findings indicate that sprint-focused training may be sufficient to elicit meaningful increases in muscle fascicle length, despite small performance change.